"I'm Not a Militant Feminist": Exploring Feminist Identities and Feminist Hesitations in the Contemporary Academy - Webber, Michelle (Atlantis, 2006)
Drawing on interviews with twenty-one university women (students, teaching assistants and faculty), I show how and to what extent university women's studies classrooms are a route to feminism. Some of the women in this study are reluctant to call themselves feminists and operate with a largely personalized version of what constitutes feminism. But rather than see this as a failure of feminism as a social movement, I argue that it is useful to attempt to see the positive effects of an individualist approach to feminism operating at the micropolitical level of agency.